Photobleaching and reorientational dynamics of dyes in a nematic liquid crystal - Nöllmann, M.; Shalom, D.; Etchegoin, P.; Sereni, J.G.; Sereni, Julián (American Physical Society, 1999)
Fil: Nöllmann, M. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina